Aktivitas antioksidan dan karakteristik masker gel peel off dari ekstrak daun mangrove (Avicennia marina): Antioxidant activity and characteristics of gel peel-off mask from mangrove leaf extract (Avicennia marina) - Hasibuan, Nirmala Efri; Azka, Aulia; Basri, Basri; Mujiyanti, Apri (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Peel-off facial masks are among the most popular facial skin care methods because they are easy to apply and do not depend on the product. Mangrove leaf extracts contain bioactive components with antioxidant activity. Mangrove leaf extract contains bioactive components with antioxidant activity, making it suitable for use as a raw material for peel-off masks. This study aimed to determine the best formulation of peel-off gel masks from Avicennia marina leaf extract, based on its antioxidant activity. A. marina leaf extract was obtained using the maceration method with a flour-to-solvent ratio of 70% ethanol (1:5). The peel-off gel mask formulation consisted of four treatments with the addition of A. marina extract: control, 0.5, 1, and 1.5%. The parameters analyzed included phytochemical testing of the extract, pH, drying time, stability, viscosity, antioxidant activity using the DPPH method, and sensory evaluation. A. marina mangrove leaf extract contains bioactive components such as flavonoids, terpenoids, steroids, tannins, and saponins. The IC50 value of A. marina leaf extract was 44.88±0.90 ppm. The best peel-off gel mask formulation was at a 1.5% ethanol extract concentration of A. marina leaves, with the best IC50 value being 336.86±4.89 ppm. The physical characteristics of the best A. marina peel-off gel mask treatment were a pH of approximately 5.5, homogeneity, drying time of 20.10 minutes, and viscosity value of 175.00 mPa. Sensory assessment of the peel-off gel mask with A. marina leaf extract showed that the parameters of appearance, aroma, color, and texture were neutral to slightly preferred by panelists. A. marina leaf extract can be applied to peel-off gel masks.